Strength and Solidification Mechanism of Silt Solidified by Polyurethane - Fengyuan Li; Chaojie Wang; Yangyang Xia; Yanjie Hao; Peng Zhao; Mingsheng Shi (Advances in Civil Engineering)
To determine the mechanism and strength characteristics of solidification of silt by a permeable polyurethane grouting material, the effects of polymer content, soil moisture, and immersion time on the unconfined compressive strength (UCS) of the silt have been studied. The results showed that the permeable polymer grouting material can significantly improve the performance of silt: (1) A higher amount of polymer produced a greater strength in the solidified soil. (2) The strength of the solidified soil increased as the immersion time was increased. (3) Moisture in the soil was not conducive to improving the strength of the solidified soil. The X-ray diffraction (XRD) and energy-dispersive spectroscopy (EDS) have proven that polyurethane does not react with the silt, but they could improve the strength of the silt through physical action. Mercury intrusion porosimetry (MIP) and scanning electron microscopy (SEM) were performed to find that polymers can reduce soil porosity, and the addition of polyurethane improved the strength of the silt mainly through adhesion, wrapping, filling, and bridging.